DESAIN DAN SINTESIS SENYAWA ACES (ANALOG CURCUMIN SERIES) DENGAN METODE SOLID PHASE REACTION SEBAGAI SENYAWA ANTIKANKER POTEN DENGAN MEKANISME MENGHAMBAT PROTEIN NF-kB - Widiapranolo, Monica Sabrina; Mayangsari, Eva; Valeria, Venny (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
Analog of curcumin in forms of enone and dienone aromatic is known for their activity as an NF-ÎºB inhibitor. In this study, will be synthesized 2-(4-N, N-dimethylamino benzilidine) cyclohexane-1,3-dione as an analog that predicted has an activity as an NF-ÎºB inhibitor. It was a non-experimental descriptive non-analytical research ehich conducted based on the crossed aldol condensation reaction by reacting 3 mmole p-N,N-dimethylamino benzaldehide and 6 mmole cyclohexane-1,3-dione with hydrochloric acid as the catalyst using solid phase reaction method. This research applied qualitative and quantitative tests. The qualitative tests consisted of organoleptic, solubility, melting point, TLC (with silica gel F254 as stationary phase and ethyl acetate: chloroform (1:5) as mobile phase), and structure elucidation with infrared spectroscopy, mass spectroscopy, and 1H-NMR. Quantitative test involved the calculation of the yield. Based on computational analysis, 2-(4-N,N-dimethylamino benzilidine) cyclohexane-1,3-dione showed a better interaction with NF-ÎºB protein with PLANTSPLP score was -69,7895. The outcome of the reaction were yellow colored powder and no odor. The yield values were 80.933%; 78.326%; and 77.229%. Its soluble in ethyl acetate and chloroform. TLC test shown the existence of new chemical substance. Liquid chromatography showed 100% purity. The melting point range were 233,7-234,6oC. The results of structure elucidation by 1H-NMR, infrared and mass spectroscopy tests indicated the compound was 2-(4-(dimetilamino)benzilidena)-4-(3-oksosiklohex-1-enil) sikloheksana-1,3-dion.Â Keywords: 2-(4-N, N-dimethylamino benzilidine) cyclohexane-1,3-dione, crossed aldol condensation, solid phase reaction, green chemistry